2002
DOI: 10.1002/jsfa.1202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen fertilisation on below‐ground carbon allocation in lettuce

Abstract: The aims of this study were to investigate the effect of nitrogen (N) fertilisation on the belowground carbon (C) translocation by lettuce and the CO 2 efflux from its rhizosphere. Two N fertilisation levels (80 and 160 kg N ha À1) and two growth stages (43 and 60 days) were tested. 14 C pulse labelling of shoots followed by 14 C monitoring in the soil, roots, microbial biomass and CO 2 efflux from the soil was used to distinguish between root-derived and soil organic matter-derived C. The 14 C allocation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…Microbial growth and enzyme production are accompanied by increased microbial demand for nutrients. Subsequently, microorganisms scavenge N from SOM and cause priming (Kuzyakov et al, 2002;Fontaine et al, 2004a;Cheng, 2009;Dijkstra et al, 2013;Paterson & Sim, 2013). This is apparent in the subtropical soil but only for single additions in the tropical soil.…”
Section: Dependence Of Priming Effects On C-addition Patternsmentioning
confidence: 99%
“…Microbial growth and enzyme production are accompanied by increased microbial demand for nutrients. Subsequently, microorganisms scavenge N from SOM and cause priming (Kuzyakov et al, 2002;Fontaine et al, 2004a;Cheng, 2009;Dijkstra et al, 2013;Paterson & Sim, 2013). This is apparent in the subtropical soil but only for single additions in the tropical soil.…”
Section: Dependence Of Priming Effects On C-addition Patternsmentioning
confidence: 99%
“…The surface of the soil was covered with a PVC board and sealed with silicon, including around the maize stems. A leak check was carried out to confirm air tightness (Kuzyakov et al 2002). A beaker containing Ba 13 CO 3 (98 at.% 13 C; 4.5, 8.5, 8.0 and 8.0 g each for the 4 labeling occasions, respectively) was placed into the chamber and an aliquot of 1 M HCl was injected into the beaker every 1.5 h for 7 h. CO 2 concentration within the chamber was semi-quantita tively detected by GXH305 infrared detector (Beijing Analytical Equipment Co.) because of the differing wavelengths for maximum absorption of 13 CO 2 and 12 CO 2 .…”
Section: Maize Growth Conditionsmentioning
confidence: 99%
“…Previous studies have also reported that the rhizodeposits of rice account for ∼ 17 % of the photoassimilates (Nguyen, 2003) that enter paddy soil and that rice rhizodeposits include soluble exudates, root border cells, dead debris, and insoluble mucilage (Lu et al, 2003). In cereal crops, 10-25 % of root exudates are incorporated into SOC, and rhizodeposits are thought to play a key role in C cycling and sequestration in plant-soil-microbe systems (Kuzyakov et al, 2002(Kuzyakov et al, , 2003. In addition to the photosynthesized C substrates of plants, soil microbes are also able to assimilate CO 2 via the Calvin-Benson-Bassham cycle, thus can significantly contribute to the net uptake and assimilation of atmospheric CO 2 as well (Ge et al, 2013;Yuan et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…So far, the effect of C input from different C sources on the balance and stability of SOC has received limited attention. For example, the C in roots and shoots occurs as particulate matter and must be first depolymerized before be-ing taken up by microorganisms, whereas rhizodeposits are immediately available for uptake and assimilation by microorganisms, which is an important step in the formation of stable organic matter (Kuzyakov et al, 2002(Kuzyakov et al, , 2003. As low molecular weight substances, rhizodeposits are also protected from mineralization via adsorption onto soil particles (Jones and Edwards, 1998;Saidy et al, 2012;Sodano et al, 2016), which contributes to the stability and sequestration of SOC (Ge et al, 2012).…”
Section: Introductionmentioning
confidence: 99%